Ultrasonic examination of the tongue shape changes in the process of articulation of vowels - Gudra, Tadeusz; Opieliński, K.J.; Sobczak, T. (Archives of Acoustics, 2006)
This paper presents results of ultrasonic examination of changes in tongue shape during the process of articulation of vowels by people (without pronunciation disorders). The position of the tongue while pronouncing a definite vowel and the influence of individual anatomical differences upon the tongue shape were examined. Results are presented as ultrasonograms obtained in the B- and TM-type presentations. The TM mode enables, among others, determining the amplitude of deflection of a point on the tongue surface during articulation that is the most change-prone at a given distance from the hyoid bone. Obtained results were used for design and construction of a tongue phantom and a mechanical setup to control the phantom shape. The proposed tongue phantom is crucial element of a natural tongue motions simulator during articulation that can be used as a major tool in therapy of deaf people, people with hearing and pronunciation disorders.